Protein diaphanous homolog 1 (Diaph1) promotes myofibroblastic activation of hepatic stellate cells by regulating Rab5a activity and TGFβ receptor endocytosis. Issue 6 (18th April 2020) - Liu, Donglian; Fu, Xinhui; Wang, Yuanguo; Wang, Xianghu; Wang, Hua; Wen, Jialing; Kang, Ningling
Abstract: TGFβ induces the differentiation of hepatic stellate cells (HSCs) into tumor‐promoting myofibroblasts but underlying mechanisms remain incompletely understood. Because endocytosis of TGFβ receptor II (TβRII), in response to TGFβ stimulation, is a prerequisite for TGF signaling, we investigated the role of protein diaphanous homolog 1 (known as Diaph1 or mDia1) for the myofibroblastic activation of HSCs. Using shRNA to knockdown Diaph1 or SMIFH2 to target Diaph1 activity of HSCs, we found that the inactivation of Diaph1 blocked internalization and intracellular trafficking of TβRII and reduced SMAD3 phosphorylation induced by TGFβ1. Mechanistic studies revealed that the N‐terminal portion of Diaph1 interacted with both TβRII and Rab5a directly and that Rab5a activity of HSCs was increased by Diaph1 overexpression and decreased by Diaph1 knockdown. Additionally, expression of Rab5aQ79L (active Rab5a mutant) increased whereas the expression of Rab5aS34N (inactive mutant) reduced the endosomal localization of TβRII in HSCs compared to the expression of wild‐type Rab5a. Functionally, TGFβ stimulation promoted HSCs to express tumor‐promoting factors, and α‐smooth muscle actin, fibronection, and CTGF, markers of myofibroblastic activation of HSCs. Targeting Diaph1 or Rab5a suppressed HSC activation and limited tumor growth in a tumor implantation mouse model. Thus, Dipah1 and Rab5a represent targets for inhibiting HSC activation and the hepatic tumor microenvironment.